Magnitude da coinfecção leishmaniose visceral e HIV e determinantes sociais da saúde na região nordeste do Brasil: uma modelagem espaço-temporal retrospectiva (2010-2018) - Reis, Erica Santos dos (2021)
Visceral leishmaniasis (VL) is a neglected tropical disease, endemic in Brazil, mainly in the Northeast region, where approximately 50% of cases has been reported. Individuals immunocompromised with the human immunodeficiency virus and or acquired immunodeficiency syndrome (HIV/AIDS) are more susceptible to the VL infection. In addition, patients co-infected with LV-HIV do not respond satisfactorily to the treatment and it significantly raises the chances of recurrences and deaths. The geographical overlap of VL and HIV contributed to an increase in the number of co-infected in the Northeast region, whose epidemiological scenario is influenced by the social determinants of health (SDH), as it is a region with important socioeconomic disparities. Therefore, the objective of this study was to analyze the spatiotemporal distribution patterns and the social determinants of health associated with VL-HIV co-infection in the Northeast region of Brazil. We conducted an ecological and time-series study using spatial analysis techniques and included all confirmed cases of VL-HIV in 1,794 municipalities from the Northeast region, between 2010 and 2018. Data were obtained from the Health Information System of Notification (SINAN). Time trends were analyzed using segmented linear regression models. The inferences of spatial statistics were performed through local empirical Bayesian analysis, Moran's global and local indexes. Additionally, we used the spatiotemporal scanning statistic to identify high-risk spatiotemporal clusters for VL-HIV, and the spatial models (simultaneous autoregressive regression - SAR and conditional autoregressive regression - CAR) to select variables associated with the occurrence of VL-HIV. We identified a total of 1,550 cases of VL-HIV in the Northeast. Interestingly, coinfection was more prevalent among men (83%), in aged 20-59 years (54.8%), inf non-white skin color (91.74 %), in low education level group (35.48%) and in residents from urban areas (80.19%). We observed increasing time trends in the VL-HIV detection rate in the state of Maranhão, and high-risk clusters were also detected in the states of Maranhão and Piauí. The annual incidence in these states was 1.3/100,000, in the period between 2014 and 2017 (Relative Risk-RR = 6.34). Considering the SDH, we observed significative correlation with the co-infection among precarious housing (C=0,62; E=0,07; p<0,001), low income (C= 0,67; E=0,09; p<0,01) and low educational level (C= 0,70; E= 0,10; p<0,02). Taken together, our data demonstrate that the VL-HIV co-infection is increasing in the Northeast of Brazil, and is, therefore, an important problem for the public health, since both diseases have raised in number of cases in the same region and mainly affect the poorest population. VL-HIV presents itself in a dispersed way in the Northeast and reaches states in conditions of social vulnerability more frequently, so it is necessary to reinforce the importance of implementing specific surveillance strategies, especially in high-risk areas, which can contribute to the reduction of cases in these populations.